Introducing the Role of Shaping Order K in Set Shaping Theory - Biereagu, Sochima (My University, 2023)
Set Shaping Theory, an emerging area of study, delves into the transformation of data sets via bijection functions. Central to this theory is the parameter K, which determines the extent of transformation, essentially reshaping the data. This article introduces the pivotal role of K in the Set Shaping Theory, shedding light on its implications for data compression and transformation dynamics.
Keywords: data compression; entropy coding; information theory; set shaping theory